2021
DOI: 10.3390/technologies9030053
|View full text |Cite
|
Sign up to set email alerts
|

MicroWorld: An Augmented-Reality Arabian App to Learn Atomic Space

Abstract: The visualization of objects of an abstract nature has always been a challenge for chemistry learners. Thus, augmented reality (AR) and virtual reality (VR) have been heavily invested in as immersive learning methods for these concepts. This study targets the segment of the chemistry curriculum involving the chemical elements of the periodic table. For this purpose, we developed the AR educational tool called MicroWorld. This Arabic educational AR app was developed in unity with Vuforia SDK. Using MicroWorld, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Peterson et al (2020) depicted an AR application used to visualize the complex three-dimensional structures of macromolecules such as proteins or DNA. Alrige et al (2021) described the development of an AR application in which students can visualize the structures of chemical elements at the submicroscopic level by using their smartphone camera to scan special cards of chemical elements. In both examples, there were clear benefits of utilizing AR-assisted visualization regarding students' interests and their understanding of 3D structures.…”
Section: Using Digital Tools For Visualizationmentioning
confidence: 99%
“…Peterson et al (2020) depicted an AR application used to visualize the complex three-dimensional structures of macromolecules such as proteins or DNA. Alrige et al (2021) described the development of an AR application in which students can visualize the structures of chemical elements at the submicroscopic level by using their smartphone camera to scan special cards of chemical elements. In both examples, there were clear benefits of utilizing AR-assisted visualization regarding students' interests and their understanding of 3D structures.…”
Section: Using Digital Tools For Visualizationmentioning
confidence: 99%
“…AR technology can be widely used as a teaching aid in the future, but only at a basic and non-holistic level (Akashah et al, 2016;Sepasgozar, 2020). As a result, AR technology can be developed and used as a learning medium in the field of education (Alrige et al, 2021;Cahyani et al, 2021). The study of Norabeerah et al ( 2012) demonstrated that AR is used in various fields such as science, astronomy, and English.…”
Section: The Impact Of Augmented Reality On Student Performancementioning
confidence: 99%
“…Despite having a positive impact, third-language effectiveness remains far behind (Akashah et al, 2016). AR technology can be used in games (Sepasgozar, 2020), language translation, vocabulary, sentence reading, and correct pronunciation (Alrige et al, 2021;Cahyani et al, 2021;Fauzan et al, 2020;Lubis et al, 2019). Thus, augmented reality (AR) is a new system that is rapidly expanding and has the potential to improve the effectiveness of teaching and learning in order to meet educational technology goals in the future (Alrige et al, 2020).…”
Section: The Impact Of Augmented Reality On Student Performancementioning
confidence: 99%